The Meaning of Love - Ortiz-Osés, Andrés (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Pavel Florensky was an outstanding Russian writer, philosopher, scientist and theologian. Born in Russia in 1882, he was executed by the soviet regime in 1937. He was influenced by Leo Tolstoy, and was a colleague of Mikhail Bulgakov. A married Orthodox priest, Florensky´s work is only recently becoming widely known, above all The Pillar and Ground of Truth. I discovered his multifaceted thought through an Italian friend, Nunzio, who gave me a copy of The polyphonic thinking of P. Florensky. I was surprised by the interest of this genuinely multi-faceted thinker, whose musical key is in the radical idea of relation, which reminded me of our own Angel Amor Ruibal, because relation separates and repairs all things and their antinomies, even if in Russian relation is constituted through symbolism, and a symbolism of platonic-christian signs. Indeed, Florensky´s Platonism is an incarnated Platonism, and thus an incarnating idealism, according to which phenomenal immanence must be joined to noumenal transcendence, and vice versa, according to the motto proper to all Christian humanism: protecting the divine is protecting the human.
Keywords: love; friendship; affection; ritual; icon; transcendence; God